EFFECTIVENESS OF CYTOLOGY FOR DIFFERENTIAL DIAGNOSIS OF MALIGNANCEES OF THE STOMACH - N. ÖRMECİ,; Y. UEİ,; M. ITABASHI,; S. YOSHIDA,; K. MARUYAMA,; Ö. UZUNALİMOĞLU, (Turkish Journal of Gastroenterology, 2020)
-